Exploring the Dynamics of Sleep Deprivation: Insights into Complete Blood Count and Coagulation Parameters in a Case-Control Study - Abd Elhadi Agena; Leena Mirghani; Abdirasak Ali Mude (Advances in Hematology)
Background. The lack of preceding research in Sudan emphasizes the importance of this study, which contributes critical data to the global understanding of sleep-related health effects. This study investigates the complex relationship between sleep deprivation and blood-related factors, particularly focusing on full blood count and coagulation parameters. Methods. From January to March 2022, a case-control study was conducted in Kosti, Sudan. A control group of 11 healthy 23–33-year-olds (6 men and 5 women) had regular sleep patterns. Six men and five women ages 23–33 were chosen for this sleep-deprived case study. The case group was deprived of sleep from 7:00 p.m. to 7:00 a.m. for three days and allowed to sleep normally during the day. Daily at 7:00 a.m., antecubital vein blood was drawn. The ACL 7000 coagulation analyzer and Sysmex fully automated hematology analyzers were used for coagulation and whole blood count analysis. Data analysis included descriptive and inferential approaches like the Mann–Whitney U test for group comparisons. Results. The study found no significant differences in total white blood cell counts reported between case and control groups (p=0.898). The case group had a substantial drop in lymphocyte counts on day 3 (p=0.016). The third day showed significant differences in neutrophil and eosinophil levels (p=0.003 and 0.000, respectively). The difference in hemoglobin and hematocrit on day 3 was statistically significant (p=0.023). Platelet counts were stable. Both groups’ prothrombin times were unaffected. On all three days, groups had significant differences in activated partial thromboplastin time (APTT) (p=0.004). Therefore, the intrinsic coagulation system may have changed. Conclusion. This study demonstrates the complex link between sleep deprivation, coagulation indicators, and complete blood count. Monitoring blood indicators in poor sleep helps explain fundamental mechanisms and medicinal implications.